(untitled) (Journal of Economic Research & Business Administration, 2016)
The article discusses the management of logistics services to provide strategic competitive advantage in today’s economy, through the rational use of resources and improving business processes of customer service. It reviewed the theoretical aspects of logistics services, the types of logistics services, tasks, functions and stages of formation of logisticheskskogo service. It is shown that the essential requirements in the way of increasing competitiveness through logistics service is to carry out external and internal audit, to determine the level of logistic service and the cost of logistics services, allowing us to provide quick response to changing market conditions. A method of forming a system of logistic service companies using the model of logistics service management system, based on the principles of the Deming cycle. This method contributes to their economic stability in the market due to logistical coordination to enable a compromise between functional units and provide them with an integrated interaction with the environment. A list of indicators to measure the quality of the components of logistics service.